La condition d’étranger : une mise en discours de la conscience de soi et de la perception de l’autre - Christian Lagarde (Cahiers de Civilisation Espagnole Contemporaine)
The condition of the alien, who confronts the other with his identities and tests them, is linked to the status of the one who moves. After a critical presentation of several theoretical approaches, the research focuses on two different corpora concerning economic Spanish and Portuguese immigrants who came at the same time to the Perpignan area (South-center of metropolitan France). The aim is to analyze, through their discursive production, the limitations of the universality of such a condition according to possible stereotypical surmises, then to show the existence of on the one hand an identity conflict between allogeneous individuals and natives, and on the other hand an identity conflict within the immigrant himself, especially when considering, although not necessarily accomplishing, a return trip to the country of origin.